2021
DOI: 10.1002/elps.202100269
|View full text |Cite
|
Sign up to set email alerts
|

Sixteen capillary electrophoresis applications for viral vaccine analysis

Abstract: A broad range of CE applications from our organization is reviewed to give a flavor of the use of CE within the field of vaccine analyses. Applicability of CE for viral vaccine characterization, and release and stability testing of seasonal influenza virosomal vaccines, universal subunit influenza vaccines, Sabin inactivated polio vaccines (sIPV), and adenovirus vector vaccines were demonstrated. Diverse CZE, CE‐SDS, CGE, and cIEF methods were developed, validated, and applied for virus, protein, posttranslati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 112 publications
0
19
0
Order By: Relevance
“…16 SDS-CGE has been widely used in the biopharmaceutical industry to analyze therapeutic proteins in a simple and robust manner for drug development and commercialization; however, limited studies have been published to date on the fundamental aspects of this transitionally cross-linked chemical gel separation matrix. 17 Understanding of the migration and separation behavior of SDS−protein complexes will aid in the optimization of the analysis of specific biopharmaceuticals. This article reports on the effect of the concentration and ratio of the dextran monomer (2 MDa) and borate cross-linker on molecular sieving and separation performance in capillary SDS gel electrophoresis of proteins.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16 SDS-CGE has been widely used in the biopharmaceutical industry to analyze therapeutic proteins in a simple and robust manner for drug development and commercialization; however, limited studies have been published to date on the fundamental aspects of this transitionally cross-linked chemical gel separation matrix. 17 Understanding of the migration and separation behavior of SDS−protein complexes will aid in the optimization of the analysis of specific biopharmaceuticals. This article reports on the effect of the concentration and ratio of the dextran monomer (2 MDa) and borate cross-linker on molecular sieving and separation performance in capillary SDS gel electrophoresis of proteins.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chemical modification in virus particles can be monitored by several methods, e.g., capillary zone electrophoresis (CZE), dynamic light scattering (DLS), and electrophoretic light scattering (ELS). 17 However, these methods only provide holistic information on virus particle levels, and cannot quantify or localize these modifications on protein or amino acid level. RP chromatography is the only currently available method that can provide information on levels of oxidation in different VPs, through changes in protein retention times or appearance of new peaks, but it cannot localize these modifications in specific methionine's or tryptophan's of the VPs.…”
Section: Development Of a Robust And Reproducible Sample Preparation ...mentioning
confidence: 99%
“…Another drawback is that it does not provide additional detailed information regarding new or unknown species. 16,17 RP chromatography is one of the most widely and longest established techniques for measuring AdV particle concentrations through quantification of VPs. In the denaturing environment of an RP mobile phase, which typically includes trifluoroacetic acid (TFA) and acetonitrile (ACN), AdV particles dissociate into DNA and VPs, thereby yielding specific viral proteome fingerprints.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Multiple reports have been published for vaccine products characterization [130][131][132][133]. For example, one study reported CZE-UV for quantification of a subunit vaccine [130].…”
Section: Analysis Of New Modality Protein Therapeuticsmentioning
confidence: 99%
“…Besides monitoring the purity and integrity of the viral particles, the method was also used to study its interaction and stoichiometry with the corresponding mAb. Other CE modes such as CGE, and SDS-CGE were reported for identification, quantification, and purity analysis of vaccine products [130][131][132][133].…”
Section: Analysis Of New Modality Protein Therapeuticsmentioning
confidence: 99%